Seni Mural Sebagai Media Kritik Sosial: Perspektif Strukturalis-Konstruktivisme - Dewa Putu Oka Prasiasa (Institut Seni Indonesia Denpasar, 2022)
The phenomenon of delivering messages through mural art occurs in the social life of the Indonesian people, and is used as a medium for social criticism in the public sphere. The purpose of this study is to find the meaning of social criticism that is carried out through the media of mural art and to find the shift in values that occurs in mural art. Based on the research objectives, this research is a qualitative research with a structuralist-constructivism approach from Pierre Bourdieu. Data were collected through observation and in-depth interviews with mural artists community. The theories used to understand, criticize, find meaning and find shifts in the value of mural art are the Habitus Theory and the Cultural Production Theory. This study found that social criticism conveyed through the media of mural art has an economic meaning, a meaning of community popularity, and a meaning of freedom. While the shift that occurred, this study found that mural art, which was originally an artist's expression as a monumental work, shifted to a commodified and contemporary work.